The Role of Theater Arts Extracurricular Activities in Boosting Students' Self-Confidence at SDN 1 Embung Kandong for the AcademicYear 2022/2023 - Ahyar Zaki; Suparlan; Abdurrahim (Formad English Foundation NTB-Jakarta, 2024)
This research was conducted with the objectives: 1) to describe how to increase the self-confidence of students at SDN 1 Embung Kandong; 2) wanted to know what the extracurricular role of the theater arts is in increasing the self-confidence of students at SDN 1 Embung Kandong; 3) to find out the difference in self-confidence of students at SDN 1 Embung Kandong who attended and those who did not take part in extracurricular theater arts. This study uses a qualitative method. The population of this study was SDN 1 Embung Kandong, the samples used as data sources were students at SDN 1 Embung Kandong who attended art galleries, teachers and mentors. The process of collecting data using observation, interviews and documentation. Based on this description, the results of the study show that: The coaching process in an effort to increase the self-confidence of students at SDN 1 Embung Kandong is carried out through extracurricular activities in theater arts. Theater arts extracurricular has a very significant role in increasing the confidence of students at SDN 1 Embung Kandong. Students who take part in extracurricular theater arts have higher self-confidence.